Pragmatism and naturalism : scientific and social inquiry after representationalism - Bagger, Matthew C. (Columbia University Press, 2018)
Distinguished scholars evaluate the contribution pragmatism can make to a viable naturalism, exploring what distinguishes pragmatic naturalism from other naturalisms. They examine pragmatism's distinctive form of nonreductive naturalism and consider its merits for the study of religion, democratic theory, and as a general philosophical orientation.